2014
DOI: 10.1109/tip.2014.2364925
|View full text |Cite
|
Sign up to set email alerts
|

No-Reference Sharpness Assessment of Camera-Shaken Images by Analysis of Spectral Structure

Abstract: The tremendous explosion of image-, video-, and audio-enabled mobile devices, such as tablets and smart-phones in recent years, has led to an associated dramatic increase in the volume of captured and distributed multimedia content. In particular, the number of digital photographs being captured annually is approaching 100 billion in just the U.S. These pictures are increasingly being acquired by inexperienced, casual users under highly diverse conditions leading to a plethora of distortions, including blur in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(18 citation statements)
references
References 44 publications
0
18
0
Order By: Relevance
“…Let B( f z φ , fˆz φ ) be the DFT coefficients at frequencies ( f z φ , fˆz φ ), and let B(0, 0) be the DC component. The contrast Con z φ and variance Var z φ of the DFT coefficients are defined on the z φ -axis, respectively, as [19] …”
Section: A Motion Direction-based Local Sharpness Measurementmentioning
confidence: 99%
See 3 more Smart Citations
“…Let B( f z φ , fˆz φ ) be the DFT coefficients at frequencies ( f z φ , fˆz φ ), and let B(0, 0) be the DC component. The contrast Con z φ and variance Var z φ of the DFT coefficients are defined on the z φ -axis, respectively, as [19] …”
Section: A Motion Direction-based Local Sharpness Measurementmentioning
confidence: 99%
“…From (19), it can be seen that the size of the motion blur window W m relies on L w . If L w is too small, we can observe only the DFT distribution on a straight line without including the spatial distribution of DFT coefficients over the spatial domain.…”
Section: ) Motion Direction Estimationmentioning
confidence: 99%
See 2 more Smart Citations
“…However, determination of the effective parameter set is an important issue. No-reference IQA algorithms [60][61][62][63][64][65][66][67][68][69][70][71][72][73][74][75][76][77] attempt to perform quality evaluation for specific type of distorted images [60][61][62] and designed specifically for JPEG or JPEG2000 compression artifacts [15]. Two prominent works by Wang et al [10] and Sheikh [9] have been reported relating to no-reference image quality assessment.…”
Section: Introductionmentioning
confidence: 99%